An exploration of media literacy in South Africa and a model for tertiary education - Pepler, E. M. (University of the Free State, 2003)
Although the discipline of media studies is not new to the broad academic field of Communication Science, the phenomenon of media literacy in the media studies landscape is not so familiar. The state of affairs pertaining to the ever-growing, ubiquitous mass media in the third millennium and its potential effects on individuals and society increasingly preoccupy many researchers and other stake-holders, particularly in view of the fact that it is virtually impossible to separate the presence and possible effects of the media from society. In short, the mass media create and maintain popular and mass culture, confirming the traditional theoretical function as .prominent carriers of culture and instruments of socialization . The transactional perspective of communication has been transposed in this thesis to the context of mass media consumers at the receiving end of mass communication via the mass media. Studies have waylaid the initial perspective of the hypodermic needle theories, in the sense that these audiences do not always seem to be completely passive and at the mercy of the mass media as so-called victims, but that these consumers actually do play an active role in terms of their selection and choice of media and formats. The latter perspective heralded the user gratification chapters in the media effects history. Media literacy, however, takes this active role even further, and aims to empower and teach ordinary people, specifically young people who are often viewed as most susceptible audiences of mass media messages, to critically evaluate and mindfully decode the mass media contents. In the face of the overwhelming volume of communication and information messages surrounding the modern-day citizen, audiences can obviously lose control of their media exposure or "diets", consequently affecting their mindful judgment of these contents. Aspects such as violence, promiscuity and uninhibited sex, swearing and profanity, crime and materialism, amongst many others, often seem to be the driving force behind the mass media producers who find themselves mostly profit- and consumer-driven, as most media formats (e.g. newspapers, magazines, radio, television, film, advertisements and the Internet) are indeed and essentially businesses who can best survive by supplying popular sensation at a price to the avid consumers. Studies on the audience's psychological relationship with the media suggest that these consumers often possibly prefer not to critically choose the contents of their media diet, but thrive on a senseless absorbing thereof for various reasons. Media literacy is already an established and independent school curriculum in most of the First World countries inter alia Canada, America, Hawaii, Britain, Scotland, France, Finland, Australia, New Zealand and Japan. However, traces of media education with the desired outcome of media literate media consumers by means of various so-called media literacy approaches and techniques, seem to be sparse in the South African context. If the phenomenon of media literacy is encountered at all, it is where mere strains of the concept are included in other subjects in order to facilitate the learning of the primary subjects such as Languages, Cultural Studies, History or Human Sciences; not necessarily comprising knowledge content and skills pertaining to the mass media itself. Media literacy is a vital life-skill for any person interacting with the profuse mass media in modern-day society, and with the necessary knowledge and development of skills, all learners can enhance their enjoyment of the mass media when they are media literate. While censorship of detrimental media content is not advised, prolific studies speculate about the link between societal problems and the mass media content, leaving media academics and scholars at an impasse with these powerful "mass cuItural agents". Media literacy activities aim to furnish learners with knowledge about the nature and characteristics of the mass media as well as specific issues such as stereotyping, gender portrayals, violence, media hegemony, the creation of mass and popular culture and other effects of the media. Learners can acquire both cognitive and emotional facilities as well as psycho-motor skills in order to access, decode, evaluate and analyze different media formats and contents. The vital conative aspect - implying the conscious choice to manage media exposure - can also be redressed when consumers become enlightened about the nature and role of the mass media. Essentially, media literacy is critical thinking applied to the mass media. Its contents aim to furnish learners with discerning capabilities, in order to eventually improve the quality of individuals' lives and promote social justice by the application of evaluation of values amongst other aspects. Ultimately, a media literate society can produce more creative, individualistic and independent-thinking citizens, thus raising the standards of a democracy in the fullest sense of the word, and giving embodiment to many of the clauses of the Constitution such as that of free speech and access to information. Metaphorically speaking, it can be asked why numerous people carefully balance their food intake, but are seldom concerned about their media diets. Health warnings about the inherent dangers of smoking, alcohol, fatty foods and cholesterol are rife, whilst education for general and ordinary media consumers about the effects of alleged "unhealthy" media content seems to be rare. In the same manner that parents teach children how to navigate the potentially dangerous realm of traffic and roads, young people and future media workers - all ordinary people indeed - should be educated how to negotiate the latent dangers of the mass media. Although literature produces many and various approaches to the teaching of media literacy, there is a prominent lack of South African academic material and research on the subject. The primary goal of this study therefore is the development of a model for teaching media literacy on a tertiary level in South Africa, and to elucidate the currently fragmented and young discipline of media literacy on an international level in the face of the many different perspectives and definitions ascribed to the subject. It is lastly suggested that this study should also be seen as a form of societal criticism, which falls in the cadre of the relationship between the mass media and its consumers. A society with critical-thinking individuals and audiences who can ask pertinent questions about the content of the mass media, can raise the quality of the mass media's content and so compel the media industries and professionals to enter into a more transactional and interactional relationship with their audiences via the media, who can learn to maintain a balanced approach to the media as a result of increased media literacy. Education about the mass media industry, its contents and possible effects is the only solution to assist consumers in not being misled continuously by the media.
Thesis (Ph.D. (Communication Studies))--University of the Free State, 2003.
Keywords: Media literacy; Mass media -- Study and teaching